2020
DOI: 10.1111/1556-4029.14268
|View full text |Cite
|
Sign up to set email alerts
|

Prodrugs of New Psychoactive Substances (NPS): A New Challenge

Abstract: The concept of a substance acting as a prodrug for an intended drug is not new and has been known and utilized with particular benefits within medicine for efficacy and patient safety. Prodrugs of psychoactive substances are also not particularly new but this has also extended to considerations of prodrugs of new psychoactive substances (NPS). The continuing evolution of NPS has been a constant forensic challenge. In some countries, this constant evolution has led to the introduction of various alternative met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…These findings were also consistent with the data reported in an intoxication where the ingestion of 1P‐LSD in blotter form did not result in its detection in either urine or serum but LSD instead 23 . In the present investigation, an incubation of 1CP‐LSD with human serum also revealed the formation of LSD when the incubation mixture was analyzed by LC‐ESI single quadrupole MS. As summarized in the Supporting Information section (analyses performed in triplicate but only one representative example shown), it was found that the signal response related to the hydrolysis product increased over time when analyzed at 0, 1, 2, 3, 5, 7, and 24 h. These results showed that 1CP‐LSD was hydrolyzed to LSD in serum but that conversion was not complete within the first 24 h. However, 1CP‐LSD is likely to be hydrolyzed at a much faster rate in vivo because humans express carboxyesterase in red blood cell membranes but not in serum 37,38 . Indeed, 1P‐LSD has been shown to undergo relatively rapid hydrolysis in vivo.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…These findings were also consistent with the data reported in an intoxication where the ingestion of 1P‐LSD in blotter form did not result in its detection in either urine or serum but LSD instead 23 . In the present investigation, an incubation of 1CP‐LSD with human serum also revealed the formation of LSD when the incubation mixture was analyzed by LC‐ESI single quadrupole MS. As summarized in the Supporting Information section (analyses performed in triplicate but only one representative example shown), it was found that the signal response related to the hydrolysis product increased over time when analyzed at 0, 1, 2, 3, 5, 7, and 24 h. These results showed that 1CP‐LSD was hydrolyzed to LSD in serum but that conversion was not complete within the first 24 h. However, 1CP‐LSD is likely to be hydrolyzed at a much faster rate in vivo because humans express carboxyesterase in red blood cell membranes but not in serum 37,38 . Indeed, 1P‐LSD has been shown to undergo relatively rapid hydrolysis in vivo.…”
Section: Resultsmentioning
confidence: 95%
“…showed that 1CP-LSD was hydrolyzed to LSD in serum but that conversion was not complete within the first 24 h. However, 1CP-LSD is likely to be hydrolyzed at a much faster rate in vivo because humans express carboxyesterase in red blood cell membranes but not in serum. 37,38 Indeed, 1P-LSD has been shown to undergo relatively rapid hydrolysis in vivo. In rats, high levels of LSD are found in the plasma 15 min after subcutaneous administration of ALD-52 and 1P-LSD, indicating they likely undergo rapid hydrolysis.…”
Section: Analytical Featuresmentioning
confidence: 99%
“…However, metabolites can conceivably contribute to the pharmacological effects of their parent drug. 210,211 An example of a parent drug with an active metabolite is oxycodone, another µ-opioid receptor agonist, which can be metabolized to oxymorphone mediated by the CYP2D6 enzyme ( Figure 15). 212 Oxymorphone is itself active at the µ-opioid receptor and listed under the 1961 Single Convention on Narcotic Drugs.…”
Section: Fentanyl Analoguesmentioning
confidence: 99%
“…Derivatives substituted with an acyl group at the N 1 position show less potency than the parent compound. Their affinity for monoamine receptors, mainly dopaminergic or serotoninergic, including 5-HT 2A , which is the most important for the effect of LSD, is lower (Halberstadt et al, 2019;Brandt et al, 2020;Elliott, Holdbrook, Brandt, 2020). Homologues of LSD with substituents in the N 6 position can show a greater potency in the case of ethyl, n-propyl, or allyl substituents or a lesser potency in the case of longer substituents, such as the n-butyl group or the isopropyl group.…”
Section: Introductionmentioning
confidence: 99%
“…it should be noted, however, that there have been considerably fewer studies of the effects of LSD derivatives than of LSD itself (Brandt et al, 2017). Compounds with a modified structure in the N 1 position are rapidly hydrolysed to LSD in the body (Brandt et al, 2020;Elliott et al, 2020;Grumann et al, 2020). 1P-ETH-LAD metabolises to ETH-LAD (Brandt et al, 2017;Brandt et al, 2020;Elliott et al, 2020), which makes it difficult to identify in the biological material the psychoactive substance administered -as the parent substance may go undetected.…”
Section: Introductionmentioning
confidence: 99%